Spin evolution and feedback of supermassive black holes in cosmological simulations. Issue 3 (14th October 2019) - Bustamante, Sebastian; Springel, Volker
ABSTRACT: It is well established that the properties of supermassive black holes (BHs) and their host galaxies are correlated through scaling relations. While hydrodynamical cosmological simulations have begun to account for the coevolution of BHs and galaxies, they typically have neglected the BH spin, even though it may play an important role in modulating the growth and feedback of BHs. Here we introduce a new sub-grid model for the BH spin evolution in the moving-mesh code arepo in order to improve the physical faithfulness of the BH modelling in galaxy formation simulations. We account for several different channels of spin evolution, in particular gas accretion through a Shakura–Sunyaev α-disc, chaotic accretion, and BH mergers. For BH feedback, we extend the IllustrisTNG model, which considers two different BH feedback modes, a thermal quasar mode for high accretion states and a kinetic mode for low Eddington ratios, with a self-consistent accounting of spin-dependent radiative efficiencies and thus feedback strength. We find that BHs with a mass M_bh10^8 M_ reach high spin values as they typically evolve in the coherent gas accretion regime, in which consecutive accretion episodes are aligned. On the other hand, BHs with a mass M_bh10^8 M_ have lower spins as BH mergers become more frequent, and their accretion discs fragment due to self-gravity, inducing chaotic accretion. We also explore the hypothesis that the transition between the quasar and kinetic feedback modes is mediated by the accretion mode of the BH disc itself, i.e. the kinetic feedback mode is activated when the disc enters the self-gravity regime instead of by an ad hoc switch tied to the BH mass. We find excellent agreement between the galaxy and BH populations for this approach and the fiducial TNG model with no spin evolution. Furthermore, our new approach alleviates a tension in the galaxy morphology–colour relation of the original TNG model.